ECONOMIC ANALISIS OF OUTDOOR RECREATION - Barkhas, Jalil (European Scientific Journal, ESJ, 2014)
The objective of the present paper is analizes important aspects related with the economics of outdoor recreation. Many of these aspects depend on the understanding of the demand for outdoor recreation in general and for determined recreational sites. We considered the general issue of the optimal visitation level at a public parks and brought in the issue of congestion cost. Also, given the growth of the population and income, the paper focused on the ration use of public parks from nonfee and fee charge for entry. Then consider the relationship between prices and revenues. Finally, the paper ended syudying the ecotourism, incuding fee options, the posible ecological impacts and the distribution of the generated rent.